The Effect of Ethnic Diversity on Expenditure Inequality in Indonesia - Martin Budi (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2020)
Based on the National Socio-Economic Survey (Susenas) and population census from 2010, this study examines the effect of ethnic diversity on expenditure inequality in Indonesia. This is achieved using the OLS estimation using ethnic fractionalization index (efi) and ethnic polarization index (epoi) as the proxy of ethnic diversity.Â Without the control variable, the ethnic fractionalization index is positive and significant in affecting expenditure inequality in Indonesia. Unlike the ethnic fractionalization index, the ethnic polarization index and expenditure inequality have an inverted U-shaped relationship. However, the effect of ethnic diversity is less significant when control variables are added to the estimation. Additionally, the effect of ethnic diversity loses its significance when incorporating regional dummies into the estimation. We found that all regional dummies significantly affect inequality and diminish the ethnic diversity effect. Finally, the inclusion of the interaction term between ethnic diversity proxy and regional dummies reveals an unexpected result. Though not significant, both interactions of the ethnic fractionalization index or the ethnic polarization index with regional dummies show a negative relationship.